Influence of Dietary Enzymes Prepared at Ensiling (ZADO®) from Hatch to 42 Days of Age on Productivity, Slaughter Traits and Blood Constituents in Broiler Chickens - Safaa , H.M. (International Journal of Poultry Science, 2013)
Four hundred Cobb-500 broiler chicks at one-day old were used to study the effects of exogenous xylanases, cellulases, protease and alpha-amylase enzyme preparations at ensiling (ZADO®) on the productive performance, slaughter traits and blood metabolites. Chicks were divided randomly into 4 treatments (broiler basal diets supplemented with 0, 2, 4 and 6‰ with ZADO®) and housed on deep litter at an open house system under commercial conditions. Each treatment replicated 4 times (30 chicks per replicate). Basal diet contained 23.1% CP and 3,103 kcal AME/kg for the starter diet (0-21 d) and 20.0% CP and 3,207 kcal AME/kg for the finisher diet (21-42 d). Results indicated that broiler productivity improved in response to dietary 4 or 6‰ ZADO®. Feed conversion ratio was 1.948, 1.903, 1.758 and 1.678 for birds fed diet supplemented with 0, 2, 4 and 6‰ ZADO® (p = 0.0007), respectively. In addition, birds fed diet supplemented with 6‰ ZADO® recorded higher dressing and immune organs relative weights at 42 days of age than other treatments (p